A Decadal Bibliometric Analysis on the Therapeutic Strategies in Oral Lichen Planus - Kumar Chandan Srivastava; Ravinder S. Saini; Galvin Sim Siang Lin; Artak Heboyan; Deepti Shrivastava (Health Science Reports)
ABSTRACT Background and Aims Oral Lichen Planus (OLP) is a common chronic inflammatory autoimmune illness that mostly affects the oral mucosa but may also affect other mucous membrane. It has higher prevalence in female patients of fourth to sixth decade of life with reticular being the commonest clinical variant. Clinical assessment, patient history, biopsy findings, and immunofluorescence were used to diagnose OLP. This study aimed to assess research publication trends in therapeutic strategies in the treatment of OLP, examining publication growth, country and institution contributions, and collaborative networks. Methods Using the Dimensions and Lens.org databases with Boolean operators combined the keywords a total of 40,046 peer‐reviewed international publications were initially assessed. The article was selected from 2014 to December 2023. Through rigorous application of inclusion and exclusion criteria using an advanced search, a subset of 134 papers emerged to meet the high relevance standards. This subset, constituting a representative sample, was selected for in‐depth bibliometric analysis. Results and Conclusion The result shows a clear upward trend in the number of publications, with a notable increase in 2018. After 2018, there is decrease in the number of publications, but it has an upward trend, reaching a peak of 215 in 2022. Chaitanya Nallan CSK leads the list of authors with four publications and a respectable total citation count of 12. Cairo University is the leading institution in this data set, with the 8 number of publications and 11 citations. The analysis revealed that at the top of the list is the “Egyptian Dental Journal” from Egypt, with six publications, four citations, and a link strength of two. In the second position is “BMC Oral Health” from the United Kingdom, with five publications, one citation, and a link strength of three. This study offers valuable insights for future research, clinical practice, and policy decisions.